Proposal for the reduction of risk in credit granting: A case study in the Colombian health sector - López Rodríguez, Campo Elías; Cruz-Linares, Judy Katherine (Cooperativismo & Desarrollo, 2021)
Credit risk plays an important role in the financial management of organizations, because it is related to the possibility of non-payment of obligations acquired by customers and in turn to mitigating this to guarantee liquidity and sustainability of the loan firm.Through a qualitative methodological approach from a documentary analysis, the current situation of the credit granting process in a company in the health sector is identified, and a periodic follow-up is developed longitudinally after the implementation of the proposal. The results determine that from the definition and implementation of credit policies, the structure of the portfolio improves by reducing the concentration in the highest ages, additionally, the collection increases and the excess in credit limits is reduced. It is concluded from this implementation that one of the main bases for obtaining financial well-being in organizations is the definition of efficient credit policies, which allow adequate profiling of clients, finding profiles with very good support and opportunity in payments.